2019
DOI: 10.1002/jcph.1515
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Models to Predict Maternal Pharmacokinetics and Fetal Exposure to Emtricitabine and Acyclovir

Abstract: Pregnancy is associated with physiological changes that may impact drug pharmacokinetics (PK). The goals of this study were to build maternal-fetal physiologically based pharmacokinetic (PBPK) models for acyclovir and emtricitabine, 2 anti(retro)viral drugs with active renal net

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…This was motivated by the fact that the pregnant PBPK model parameterization served as starting point for the physiological alterations during the postpartum period thereby allowing an evaluation of these physiological parameters prior to the onset of labor. Similar to previous pregnancy PBPK models for predominantly renally cleared drugs [22,23], the herein presented model predicted amoxicillin PK adequately which further increases the credibility of the pregnancy PBPK model.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This was motivated by the fact that the pregnant PBPK model parameterization served as starting point for the physiological alterations during the postpartum period thereby allowing an evaluation of these physiological parameters prior to the onset of labor. Similar to previous pregnancy PBPK models for predominantly renally cleared drugs [22,23], the herein presented model predicted amoxicillin PK adequately which further increases the credibility of the pregnancy PBPK model.…”
Section: Discussionsupporting
confidence: 78%
“…Previously, a pregnancy PBPK model has been developed in the OSP software package and evaluated for various drugs [22,23,[33][34][35]; amoxicillin is not part of the previously modeled drugs. Here, this generic model was applied to develop an additional substance model for amoxicillin to predict the disposition of intravenously administered amoxicillin prior to child birth.…”
Section: Pregnancy Pbpk Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…While D pl was not a sensitive parameter for acetaminophen, future studies could test high permeability compounds with high K f,m values to generate more knowledge about the validity of predicting D pl via different approaches. Overall, the results of the comparison of the different approaches for estimating placental transfer are in line with a recently published study on emtricitabine and acyclovir that demonstrated that fetal exposure can be adequately predicted when placental transfer is informed either by the ex vivo cotyledon experiment or by the approach by Liu et al [54]. Still, more research on other drugs with a K f,m approximating 1.0 and high permeability is clearly needed to further build confidence.…”
Section: Discussionsupporting
confidence: 74%
“…9 Pharmacokinetic (PK) models have been constructed to predict fetal exposure using transplacental transfer parameters obtained from ex vivo human placental perfusion systems for various drugs, including tenofovir, emtricitabine (De Sousa Mendes et al, 2016), nevirapine (De Sousa Mendes et al, 2017), and acyclovir (Liu et al, 2019) in closed systems, paroxetine, antipyrine (Nagai et al, 2013), fluvoxamine (Matsuoka et al, 2017), and ketoprofen (Tanaka et al, 2017) in open systems, and darunavir (Schalkwijk et al, 2018) in a hybrid system (closed-open system). However, in those studies, the transplacental transfer of test drugs was mostly mediated by passive diffusion, and thus the contribution of transporter(s) to the clearance was not estimated.…”
Section: Downloaded Frommentioning
confidence: 99%